THE FIRST ATHLETIC GAMES AND THE FIRST COSTA RICAN PEDESTRE RACE. SAN JOSE 1905 - Lobo Di Palma, Jorge (2021)
At the end of the 19th century, Costa Rica was experiencing a cultural project proposed by the liberals of the time, in which it sought to create a modern national identity, influenced to a great extent by those Costa Rican intellectuals who studied in Europe, and who came with ambitious projects. modernization, which included deportes practice.Therefore, the objective of this historical semblance is to rescue as part of the historical memory of Costa Rican deportes, the first athletic games held in the country at the beginning of the 20th century. The activity included 14 events, including track and field tests and also the first recorded foot test.For the realization of this event, the first athletic track in the country was built in La Sabana, leaving a permanent legacy to this day. The games were so well organized that the participation of women was included. Some of these tests are still valid today at the national and international level, which would allow further research on the technical and historical evolution of athletics in Costa Rica.